Implementation Of The Policy On Tobacco Excise Revenue-Sharing Funds In The Crackdown On Illegal Goods - Yoyoh Supriyatin; Siti Khumayah; Sri Wulandari (ann4publisher@gmail.com, 2026)
Background. The issues surrounding the implementation of the Tobacco Excise Revenue Sharing Policy include the continued distribution of illegal excise goods in Cirebon Regency; the suboptimal implementation of the policy in promoting the destruction of illegal cigarettes; and a lack of public awareness regarding the dangers and negative impacts of illegal cigarettes. Aims. The objective of this study is to examine the implementation of the Tobacco Excise Revenue Sharing Fund (DBHCHT) policy in the destruction of illegal excise-taxed goods in Cirebon Regency. The research focuses on the implementation of law enforcement programs funded through the DBHCHT, particularly in efforts to eradicate the circulation of illegal cigarettes. Methods. The study employed qualitative methods through interviews, observations, and documentation at the Cirebon Regency Civil Service Police Unit (Satuan Polisi Pamong Praja), as the primary implementing agency. Data analysis utilized the Miles, Huberman, and Saldana model, while the policy implementation analysis framework was based on George C. Edwards III’s theory—namely, resources, dispositions, communication, and bureaucratic structure. Result. The study noted that the implementation of the DBHCHT policy in combating illegal excise goods has proceeded fairly well through information-gathering activities, public outreach, and joint operations with the Customs and Excise Office. In terms of communication, interagency coordination has been carried out routinely, although public awareness remains uneven. Regarding resources, DBHCHT budget support has contributed to program implementation, but its execution is constrained by limited personnel. Meanwhile, in terms of bureaucratic structure, a clear division of tasks is in place through interagency cooperation mechanisms, although operational coordination still needs improvement. Conclusion. The study concludes that the implementation of the DBHCHT policy in combating illegal excise goods in Cirebon Regency is fairly effective but not yet optimal. There is a need to increase resource capacity, strengthen interagency coordination, and enhance community participation in order to curb the circulation of illegal cigarettes in a sustainable and targeted manner.